THE EFFECT OF BRAND IMAGE, PRICE AND PERCEIVED QUALITY ON CUSTOMER PURCHASE INTENTION IN PLANET SURF, MANADO - Kaunang, Pingkan Theodora (Universitas Sam Ratulangi, 2013)
This day, there are so many products offered in the market. The customers sometime confuse in choosing which one to buy since the product that being offers is quite the same. What makes the product different is the price of the product, the brand of the product and he most important is the quality. This research is conduct in Planet Surf Manado. The objectives of this research are to analyze the Influence of Brand Image, Price and Perceive Quality on Customer Purchase Intention in Planet Surf Manado, partially and simultaneously. This research uses Causal type of research where it will investigate the Influence of Brand Image, Price and Perceive Quality on Customer Purchase Intention in Planet Surf Manado. This research is using a multiple regression model to answer the research problem. The population in this study is a customer of Planet Surf Manado, whereas samples taken by each respondent 100 respondents. Based on the hypothesis testing, this research conduct a conclusion of there is a significant influence of Brand Image, Price and Perceived Quality simultaneously and partially on Customer Purchase Intention in Planet Surf Manado. Based on this research, customers in Manado should have more information to be learned about the influence of brand image, price and perceived quality before they buy that product on Planet Surf and it is also expected this current research can be useful for the future development of Planet Surf in the future. Keywords: brand image, price, perceived quality, purchase intention